Corruption in Procurement Auctions - Yvan Lengwiler; Elmar G. Wolfstetter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
We review different kinds of corruption that have been observed in procurement auctions and categorize them. We discuss means to avoid corruption, by choice of preferable auction formats, or with the help of technological tools, such as secure electronic bidding systems. Auctions that involve some soft elements, such as complex bids consisting of technical and financial proposals, are particularly prone to corruption. We do not believe that it is possible to eradicate corruption altogether in such situations, but we discuss means to make it less likely.
urn:nbn:de:bvb:19-epub-13461-9
Keywords: 330